Is the Implementation of Risk Management Just a Formality? Evidence from a Public Sector Organization - Khikmatun Nafi’ah; Nurkholis Nurkholis; Abdul Ghofar (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
This study aims to describe the implementation of risk management and explore the perceptions of risk owners about its impact. This research was conducted at the Ministry of Public Works and Housing, especially in the service unit for procuring goods and construction services, considering the large budget and the number of auction packages. The research was designed as qualitative research with a case study approach. Data collection uses in-depth interviews to explore phenomena related to implementing risk management in these public sector organizations—data analysis using the Interactive Data Model. The research results show that implementing risk management is not only seen as a mere formality but as a necessity for the organization. In these public sector organizations, the effectiveness in implementing risk management is, on average, in the defined category, which means it is effective in creating and protecting organizational value. Although risk management is still carried out partially, the overall risk management system has begun to be structured and realized. On the other hand, there are still obstacles in risk management infrastructure, such as the unavailability of a risk management information system, limited understanding of risk management, and the absence of a specific budget related to risk management. In overcoming this problem, the solutions offered are to build a risk management information system, conduct education and training, and allocate a specific budget for risk management.